2012
DOI: 10.3892/mmr.2012.786
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ornithine decarboxylase alters the roscovitine-induced mitochondrial-mediated apoptosis in MCF-7 breast cancer cells

Abstract: Abstract. Polyamines (PAs) are small aliphatic amines that play a major role in multicellular functions. The PA levels are controlled by ornithine decarboxylase (ODC), the rate limiting enzyme of PA biosynthesis. α-difluoromethylornithine (DFMO) is the ODC inhibitor, which has been shown to act as an antiproliferative agent in human cancer cells by irreversibly inhibiting ODC, which is overexpressed in breast cancer cells. Roscovitine (ROSC; CYC202), a selective cyclin-dependent kinase inhibitor, induces cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In addition, several anti-oxidant agents including vitamin E are able to induce apoptosis in cancer cells [ 37 ]. Similar to other CDK inhibitors flavopiridol and roscovitine [ 38 , 39 ], dinaciclib also can enhance the intracellular ROS levels, and NAC pretreatment dramatically blocks ROS generation but partially rescues dinaciclib-induced apoptosis in the current study. Our results suggest that dinaciclib is able to prompt both ROS dependent and independent apoptosis in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, several anti-oxidant agents including vitamin E are able to induce apoptosis in cancer cells [ 37 ]. Similar to other CDK inhibitors flavopiridol and roscovitine [ 38 , 39 ], dinaciclib also can enhance the intracellular ROS levels, and NAC pretreatment dramatically blocks ROS generation but partially rescues dinaciclib-induced apoptosis in the current study. Our results suggest that dinaciclib is able to prompt both ROS dependent and independent apoptosis in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 63%
“…Conversely, suppression of ODC expression is associated with decreased cell proliferation, increased apoptosis and decreased expression of genes affecting tumor invasion and metastasis. 27 , 28 Our data showed that when ODC expression in ESCC cells was knocked down, both proliferation and anchorage-independent growth of ESCC cells were significantly suppressed (Fig. 2c, d ).…”
Section: Discussionmentioning
confidence: 71%
“…Studies showed that DFMO is effective in preventing pancreatic cancer in genetically engineered KRAS mice [ 110 ] and furthermore that the combination therapy of ODC and polyamine transport inhibition in pancreatic cancer cell lines and pancreatic cancer mouse models inhibited cancer cell survival and prolonged the survival of tumor bearing mice [ 106 , 108 ]. Other areas of prolific research include but are not limited to skin, endometrial, and breast cancer [ 111 , 112 , 113 , 114 , 115 , 116 ]. Clinical trials with DFMO are ongoing for prostate cancer, skin cancer and precancerous conditions, gastric cancer, bladder cancer, the rare brain cancer anaplastic astrocytoma, cervical cancer, and esophageal cancer ( ).…”
Section: Neuroblastomamentioning
confidence: 99%